2017
DOI: 10.1088/1742-6596/794/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Classification of different types of beer according to their colour characteristics

Abstract: Abstract. Twenty-two samples from different beers have been investigated in two colour systems -XYZ and SIELab -and have been characterised according to their colour parameters. The goals of the current study were to conduct correlation and discriminant analysis and to find the inner relation between the studied indices. K-means cluster has been used to compare and group the tested types of beer based on their similarity. To apply the K-Cluster analysis it is required that the number of clusters be determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In what follows, the authors outline the research findings exploring those visual appearance cues that influence people's expectations associated with, and the multisensory flavour perception of, beer. Although there is research exploring, for example, how (a) participants use beer colour to classify different types of beer (e.g., Nikolova, Gabrovam, Boyadzhiev, Pisanova, Ruseva, & Yanakiev, 2017), (b) training influences people's ability to sort beers (e.g., Honoré-Chedozeau, Desmas, Ballester, Parr, & Chollet, 2019;Lelièvre, Chollet, Abdi, & Valentin, 2009 1 ;Spence, 2019a), and (c) colour influences the perception of non-alcoholic birch beer (i.e., root beer) (Hyman, 1983), it is surprising how few published studies have actually assessed the expectations associated with beer, and the influence of visual appearance cues including colour on the perception of beer.…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, the authors outline the research findings exploring those visual appearance cues that influence people's expectations associated with, and the multisensory flavour perception of, beer. Although there is research exploring, for example, how (a) participants use beer colour to classify different types of beer (e.g., Nikolova, Gabrovam, Boyadzhiev, Pisanova, Ruseva, & Yanakiev, 2017), (b) training influences people's ability to sort beers (e.g., Honoré-Chedozeau, Desmas, Ballester, Parr, & Chollet, 2019;Lelièvre, Chollet, Abdi, & Valentin, 2009 1 ;Spence, 2019a), and (c) colour influences the perception of non-alcoholic birch beer (i.e., root beer) (Hyman, 1983), it is surprising how few published studies have actually assessed the expectations associated with beer, and the influence of visual appearance cues including colour on the perception of beer.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than focus on such hypothetical scenarios, our measures detail the contributions of Michigan's beer production value chains to existing economic activities. Our findings suggest that Michigan-produced beers generate a sizeable contribution to the state economy, contributing just under $500 million to the annual Gross State Product (a measure of total income generated in the state), or alternatively, 8.4 percent of the value of Michigan's food and beverage and tobacco products manufacturing sector's annual Gross State Product [45].…”
Section: Discussionmentioning
confidence: 86%
“…Before the end of fermentation and maturation, a large amount of the polyphenolic material and protein had been removed by adhesion and coagulation, and it had then sunk to the bottom of the fermenter, hence the drop in total polyphenols of beer. However, they were still present in the final beer where they contributed in determining its quality since polyphenols contribute to flavor, astringency, the perception of bitterness, haze, oxidative effects, and antioxidative effects [43][44][45].…”
Section: Total Polyphenolsmentioning
confidence: 99%
“…Along with conventional analytical methods of color determination, digital image analysis has been demonstrated to be a suitable method for classifying beer of the same type or category. Nikolova et al [45] reported the use of digital image analysis and spectrophotometer for beer type classification according to their color. For this purpose, several beer samples were chosen to obtain digital images: light beer, dark beer, a beer with lemon and beer with fruits.…”
Section: Perception and Measuring Of Beer Colormentioning
confidence: 99%